The influence of work life balance and job stress on the performance of generation y and z employees at pt aerofood Indonesia Surabaya Unit - Muyasaroh Muyasaroh; Arif Hidayat (Jurnal Mantik, 2026)
This study was conducted to analyze the relationship between work-life balance and work stress variables on the performance of Generation Y and Generation Z employees at PT Aerofood Indonesia Unit Surabaya. The data collection process was carried out using quantitative methods through the distribution of questionnaires and observations to 44 respondents selected using purposive sampling techniques with the help of the IBM SPSS Statistics application for Windows version 26. The results of the study indicate that the work-life balance variable has a positive andssignificant effect on employee performance with a t-value of 4.604 and a significance value of 0.000 <0.05. Meanwhile, the work stress variable does not show a significant effect on employee performance with a t-value of 0.307 and a significance value of 0.760 >0.05. However, simultaneously, the work-life balance and work stress variables simultaneously have a significant effect on employee performance with a calculated F-value of 11.796 and a significance value of 0.000 <0.05. The results of this study are expected to help companies evaluate and create a more balanced work environment to improve employee productivity and performance quality